Comparative evaluation of a rapid diagnostic test, an antibody ELISA, and a pLDH ELISA in detecting asymptomatic malaria parasitaemia in blood donors in Buea, Cameroon - Tebit Emmanuel Kwenti; Longdoh Anna Njunda; Beltine Tsamul; Shey Dickson Nsagha; Nguedia Jules-Clement Assob; Kukwah Anthony Tufon; Dilonga Henry Meriki; Enow George Orock (BMC, 2017)
Abstract Background In malaria endemic areas, infected blood donors serve as a source of infection to blood recipients, which may adversely affect their prognosis. This necessitates the proper screening of blood to be used for transfusion in these areas. The purpose of this study was to determine the prevalence of malaria parasitaemia in blood donors in Buea, Cameroon, and to evaluate the performance of a rapid diagnostic test (RDT), a malaria antibody enzyme-linked immunosorbent assay (ELISA), and a Plasmodium lactate dehydrogenase (pLDH) ELISA in the detection of asymptomatic malaria parasitaemia in the target population. Methods In a prospective study conducted between September 2015 and June 2016, 1 240 potential blood donors were enrolled. The donors were screened for malaria parasites using Giemsa microscopy (GM) and a RDT. A sub-sample of 184 samples, comprising 88 positive and 96 negative samples, were selected for the evaluation of the pLDH ELISA and the antibody ELISA. The chi-square test and correlation analysis were performed as part of the statistical analyses. The statistical significance cut-off was set at P < 0.05. Results The prevalence of malaria parasitaemia in this study was found to be 8.1% (95% CI: 6.6 - 9.7). The prevalence was not observed to be dependent on the age or sex of the participants. The RDT had a sensitivity (88.0%), specificity (99.1%), and negative predictive value (99.0%) higher than the ELISAs. The performance of the pLDH ELISA, which demonstrated the highest positive predictive value (91.6%), was generally comparable to the RDT. The sensitivity was lowest with the antibody ELISA (69.9%), which also demonstrated the highest false positive and false negative rates. The detection threshold for the pLDH (three parasites/μl) was lower compared to the RDT (50 - 60 parasites/μl). Non-significant positive correlations were observed between the parasite density and the pLDH titers and malaria antibody titers. Conclusions Overall, the RDT and the pLDH ELISA demonstrated a perfectly correlated agreement with GM, meanwhile the antibody ELISA demonstrated a substantially correlated agreement with GM. The pLDH is therefore recommended for mass screening of blood (to detect malaria parasitaemia) for transfusions in the study area. However, where this is not feasible, an RDT will suffice.